Association between distressing non-work-related events and occupational injuries - Cordeiro, R. (Chemical Industry Press, 2000)
The following is a report on a case-control study whose objective was to investigate the association between distressing non-work-related events and occupational injures. Ninety three injured workers (cases) were matched with 372 non-injured controls in a large metallurgical factory in southeastern Brazil. Exposure to distressing non-work-related events was measured through a questionnaire focusing on situations pertaining to personal problems unrelated to work activities. The data were analyzed by adjusting a conditional logistic regression model, where occurrence of the work injury was the dependent dichotomous variable and answers from the questionnaire were independent continuous variables. The analysis showed an association between some distressing non-work-related events and occupational injuries. These findings imply expanding the horizon of preventive measures used in targeting. work injuries which have traditionally been focused on the control of strictly workplace risks.